Validity and reliability of a health care service evaluation instrument for tuberculosis - Scatena, Lucia Marina; Wysocki, Anneliese Domingues; Beraldo, Aline Ale; Magnabosco, Gabriela Tavares; Brunello, Maria Eugênia Firmino; Netto, Antonio Ruffino; Nogueira, Jordana de Almeida; Silva Sobrinho, Reinaldo Antonio; Brito, Ewerton William Gomes; Alexandre, Patricia Borges Dias; Monroe, Aline Aparecida; Villa, Tereza Cristina Scatena (Revista de Saúde Pública, 2015)
OBJECTIVE To evaluate the validity and reliability of an instrument that evaluates the structure of primary health care units for the treatment of tuberculosis.METHODS This cross-sectional study used simple random sampling and evaluated 1,037 health care professionals from five Brazilian municipalities (Natal, state of Rio Grande do Norte; Cabedelo, state of Paraíba; Foz do Iguaçu, state of Parana; Sao José do Rio Preto, state of Sao Paulo, and Uberaba, state of Minas Gerais) in 2011. Structural indicators were identified and validated, considering different methods of organization of the health care system in the municipalities of different population sizes. Each structure represented the organization of health care services and contained the resources available for the execution of health care services: physical resources (equipment, consumables, and facilities); human resources (number and qualification); and resources for maintenance of the existing infrastructure and technology (deemed as the organization of health care services). The statistical analyses used in the validation process included reliability analysis, exploratory factor analysis, and confirmatory factor analysis.RESULTS The validation process indicated the retention of five factors, with 85.9% of the total variance explained, internal consistency between 0.6460 and 0.7802, and quality of fit of the confirmatory factor analysis of 0.995 using the goodness-of-fit index. The retained factors comprised five structural indicators: professionals involved in the care of tuberculosis patients, training, access to recording instruments, availability of supplies, and coordination of health care services with other levels of care. Availability of supplies had the best performance and the lowest coefficient of variation among the services evaluated. The indicators of assessment of human resources and coordination with other levels of care had satisfactory performance, but the latter showed the highest coefficient of variation. The performance of the indicators “training” and “access to recording instruments” was inferior to that of other indicators.CONCLUSIONS The instrument showed feasibility of application and potential to assess the structure of primary health care units for the treatment of tuberculosis.